Layoffs, Top Executive Pay, and Firm Performance - Hallock, Kevin F. (American Economic Review, 1998)
This paper examines the connection between layoffs, executive pay, and stock prices. Firms that announce layoffs in the previous year pay their CEOs more, and give their CEOs larger percentage raises than firms which do not have at least one layoff announcement in the previous year. However, the likelihood of announcing a layoff varies dramatically along other dimensions, for example firm size, which are also correlated with CEO pay. Once firm-specific fixed effects are controlled for, the CEO pay premium for laying off workers disappears. In addition, there is a small negative share price reaction to layoff announcements.